Smart Agriculture: Optimizing Soybean Cultivation Through Technology In Crop Monitoring - Sujadi, Harun; Marina, Ida; Koswara, Engkos; Rakhmi Indriana, Kovertina; Sukmawati, Dety (Greenation Research & Yayasan Global Resarch National, 2023)
The objective of this study is to optimise the productivity of soybean production through the integration of agricultural technologies inside plant monitoring systems. The objective of incorporating technology is to enhance the monitoring and management processes of soybean crops, with the ultimate goal of improving productivity and boosting harvest yields.This paper presents a proposal for the use of diverse agricultural technologies, including soil sensors, environmental sensors, drones, and data analysis based on artificial intelligence. Soil and environmental sensors are utilised for the purpose of monitoring soil conditions, moisture levels, and weather conditions in the vicinity of soybean agricultural fields. Drones are employed for comprehensive terrestrial surveillance and prompt identification of botanical concerns. The utilisation of artificial intelligence in data analysis involves the processing of information gathered from sensors and drones, enabling the provision of real-time insights and recommendations to farmers.By incorporating these agricultural technologies, it is anticipated that farmers would be able to effectively and efficiently utilise resources such as water, fertilisers, and pesticides, ensuring optimal usage in terms of precision and timeliness. Furthermore, the implementation of precise monitoring techniques and prompt responses to alterations in plant conditions within agricultural settings can effectively mitigate the potential hazards associated with crop loss resulting from pest or disease infestations.